English Englsih - Berlian, Hangrengga; Hibnu Nugroho; Kuat Puji Prayitno; Budiyono; Heradhyaksa, Bagas (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
The coordination between the military and civilian justice systems in Indonesia in handling the joinder of parties in criminal cases continues to face various challenges. This study aims to evaluate the effectiveness of the joinder of parties mechanism in strengthening law enforcement by examining the roles of military prosecutors (JAMPIDMIL) and public prosecutors. The research adopts a normative legal approach, involving a qualitative analysis of the implementation of relevant laws and regulations. The findings indicate that although Presidential Regulation Number 15 of 2021 concerning JAMPIDMIL has facilitated greater integration between the military and civilian justice systems, procedural inconsistencies and limited resources hinder effective coordination. The prosecution process is further complicated by conflicting jurisdictional determinations between the two systems. These issues, along with a fragmented legal framework and complex procedures, make the theory of an Integrated Criminal Justice System difficult to implement optimally. To address these challenges, a comprehensive strategy is required, including the establishment of a special committee to draft Standard Operating Procedures (SOPs), regulatory reform, and the enhancement of human resource capabilities through targeted training. JAMPIDMIL must be empowered under strict supervision to prevent any misuse of authority. These measures are expected to improve efficiency, facilitate the transfer of cases between military and civilian courts, and enhance legal certainty in joinder cases. Despite regulatory progress, aligning the prosecution functions of military auditors and public prosecutors still demands continuous and concerted efforts to achieve higher standards of justice